Changes in Job Security and Mental Health: An Analysis of 14 Annual Waves of an Australian Working-Population Panel Survey - LaMontagne, Anthony Daniel; Too, Lay San; Punnett, Laura; Milner, Allison Joy (My University, 2021)
We examined whether job security improvements were associated with improvements in mental health in a large, nationally representative panel study in Australia. We used both within-person fixed effects (FE) and random effects (RE) regression to analyze data from 14 annual waves covering the calendar period of 2002–2015 (19,169 persons; 106,942 observations). Mental Health Inventory–5 scores were modeled in relation to self-reported job security (categorical, quintiles), adjusting for age, year, education, and job change in the past year. Both FE and RE models showed stepwise improvements in Mental Health Inventory–5 scores with improving job security, with stronger exposure-outcome relationships in the RE models and for men compared with women. The RE coefficients for improvements in job security in men were 2.06 (95% confidence interval (CI): 1.67, 2.46) for 1 quintile, steadily increasing for 2- (3.94 (95% CI: 3.54, 4.34)), 3- (5.82 (95% CI: 5.40, 6.24)), and 4-quintile (7.18 (95% CI: 6.71, 7.64)) improvements. The FE model for men produced slightly smaller coefficients, reaching a maximum of 5.55 (95% CI: 5.06, 6.05). This analysis, with improved causal inference over previous observational research, showed that improving job security is strongly associated with decreasing depression and anxiety symptoms. Policy and practice intervention to improve job security could benefit population mental health.
American Journal of Epidemiology
Keywords: Health and wellbeing; Labour market